The Influence of Strata on the Nutrient Recycling within a Tropical Certified Organic Coffee Production System. (2012) - Mamani-Pati, F.; Clay, D. E.; Clay, S. A.; Smeltekop, H.; Yujra-Callata, M. A.
Abstract : In tropical Bolivia coffee plantations, the plant community can be separated into high (trees), middle (coffee), and low (weed) strata. Understanding the importance of each stratum is critical for improving the sustainability of the system. The objective of this study was to determine the importance of strata on nutrient recycling. Litter falls from the upper and middle strata were collected monthly using cone-shaped traps and divided by species into leaves, branches, flowers, and fruits. Dry biomass additions to the soil from high and middle strata totaled 12, 655 kg (ha yr) −1 annually. About 76% of the biomass was provided by plants of the genus Inga ( I. adenophylla and I. oerstediana ). The middle stratum ( Coffea arabica L.) provided 24% litterfall biomass. This stratum also produced 1, 800 kg coffee bean per ha (12% moisture) which sold for $2.94 kg −1 . In the lower stratum, Oxalis mollissima returned 36 kg N ha −1, while Solanum nodiflorum returned 49 kg K ha −1, and Urtica sp. returned 18 kg Ca ha −1 . The nutrients recycled through plants in three strata exceeded the amount of nutrients removed in green coffee beans.